Psychological and demographic characteristics of 368 patients with dissociative seizures: data from the CODES cohort. Issue 14 (11th October 2021) - Goldstein, Laura H.; Robinson, Emily J.; Mellers, John D. C.; Stone, Jon; Carson, Alan; Chalder, Trudie; Reuber, Markus; Eastwood, Carole; Landau, Sabine; McCrone, Paul; Moore, Michele; Mosweu, Iris; et al.
Abstract: Background: We examined demographic, clinical, and psychological characteristics of a large cohort ( n = 368) of adults with dissociative seizures (DS) recruited to the CODES randomised controlled trial (RCT) and explored differences associated with age at onset of DS, gender, and DS semiology. Methods: Prior to randomisation within the CODES RCT, we collected demographic and clinical data on 368 participants. We assessed psychiatric comorbidity using the Mini-International Neuropsychiatric Interview (M.I.N.I.) and a screening measure of personality disorder and measured anxiety, depression, psychological distress, somatic symptom burden, emotional expression, functional impact of DS, avoidance behaviour, and quality of life. We undertook comparisons based on reported age at DS onset (<40 v. ⩾40), gender (male v. female), and DS semiology (predominantly hyperkinetic v. hypokinetic). Results: Our cohort was predominantly female (72%) and characterised by high levels of socio-economic deprivation. Two-thirds had predominantly hyperkinetic DS. Of the total, 69% had ⩾1 comorbid M.I.N.I. diagnosis (median number = 2), with agoraphobia being the most common concurrent diagnosis. Clinical levels of distress were reported by 86% and characteristics associated with maladaptive personality traits by 60%. Moderate-to-severe functional impairment, high levels of somatic symptoms, and impaired quality of life were also reported. Women had a younger age at DS onset than men. Conclusions: Our study highlights the burden of psychopathology and socio-economic deprivation in a large, heterogeneous cohort of patients with DS. The lack of clear differences based on gender, DS semiology and age at onset suggests these factors do not add substantially to the heterogeneity of the cohort.